Comparative Analysis Between High Level Architecture (HLA) and Service Oriented Architecture (SOA) in the Field of Military Modelling and Simulation - Iagăru Elena-Lavinia (Scientific Bulletin, 2022)
Modelling and simulation is a major area of interest for states and international organizations in the context of the operational environment characterized by complexity, dynamism and unpredictability. At the moment, in NATO, the standard architecture for the field of modelling and simulation is High Level Architecture (HLA), but lately the concept of Service Oriented Architecture (SOA) has aroused the interest of specialists within the Alliance. In this paper, a comparative analysis is performed between the two types of architectures in order to determine the optimal variant for the field of military modelling and simulation. Following the analysis, it was concluded that a combined approach of the two types of architectures is needed to maximize the efficiency of modelling and simulation applications.